P06.07 CXCR6 expression enhances accumulation of anti-mesothelin CAR T cells at the tumor site and their therapeutic efficacy in pancreatic cancer xenografts. (1st October 2020) - Stoiber, S; Lesch, S; Ogonek, J; Cadilha, B; Benmebarek, M; Gottschlich, A; Metzger, P; Hörth, C; Nottebrock, A; Endres, S; Kobold, S
Abstract : Background: Chimeric antigen receptor (CAR) T cell therapy is currently approved for the treatment of some hematological malignancies. However, CAR T cells have so far lacked efficacy in the treatment of solid tumors. A major hurdle of CAR T cell therapy is the limited infiltration of CAR T cells into tumor tissue. Chemokine receptors enable immune cells to migrate along a chemokine gradient. Here, we show that overexpression of the C-X-C chemokine receptor 6 (CXCR6) enhances CAR T cell accumulation in C-X-C motif ligand 16 (CXCL16)-positive xenograft pancreatic cancer models, resulting in increased anti-tumor potency of anti-mesothelin CAR T cells. Materials and Methods: Human T cells were retrovirally transduced with an anti-mesothelin CAR and CXCR6. NSG mice were injected subcutaneously with mesothelin-CXCL16-overexpressing tumor cells. Mice were treated once with CAR-, CAR-CXCR6- or mock-transduced T cells when tumors were palpable and tumor size was monitored with a caliper. In a separate tracking experiment, subcutaneous tumors were established as described above and the presence of T cells at the tumor site was determined by FACS analysis within one week after adoptive T cell transfer. For orthotopic xenograft experiments mesothelin-CXCL16-overexpressing tumor cells were directly injected into the pancreas of NSG mice and one-time treatment with CAR-, CAR-CXCR6- or mock T cells was performed 5 days post tumor injection. Results: In a subcutaneous xenograft model of pancreatic cancer CXCR6-expressing CAR T cells displayed improved anti-tumoral potency compared to CAR T cells without CXCR6, resulting in prolonged survival of mice and tumor clearance in 9 out of 10 CAR-CXCR6-treated mice. A tracking experiment confirmed the increased accumulation of CAR-CXCR6 T cells compared to CAR T cells at the subcutaneous tumor site, suggesting increased migratory capacity of CAR-CXCR6-transduced T cells towards CXCL16-expressing tumors as the mode of action. Treatment of orthotopic pancreatic cancer xenografts similarly revealed prolonged survival of CAR-CXCR6-treated animals in comparison to CAR-treated animals, suggesting improved anti-tumor efficacy of CAR-CXCR6-transduced T cells. Conclusions: Forced expression of CXCR6 in anti-mesothelin CAR T cells increased the accumulation of CAR T cells at the CXCL16-positive tumor site, resulting in improved survival of treated mice and in complete tumor rejection in the majority of cases. This data reveals the potential of CXCR6 to direct CAR T cells to the tumor site and this approach may therefore be an attractive strategy to target a major pitfall in the translation of CAR T cell therapy to solid tumors. Disclosure Information: S. Stoiber: None. S. Lesch: None. J. Ogonek: None. B. Cadilha: None. M. Benmebarek: None. A. Gottschlich: None. P. Metzger: None. C. Hörth: None. A. Nottebrock: None. S. Endres: None. S. Kobold: None.